SERVICE QUALITY: Understanding customer Perception and Reaction, and Its Impact on Business - Nelson Oly Ndubisi (Gadjah Mada International Journal of Business, 2003)
This paper is an attempt to explain the process and outcomes of customer services levels and how they shape customer perceptions (of their relationship with services providers) and reactions. As an entirely conceptual work, this paper proposes a model for understanding the pathway and the end of good and bad customer service. Implications of the study on theory and practice are discussed.